2023
DOI: 10.1002/chem.202300223
|View full text |Cite
|
Sign up to set email alerts
|

Black Titania and Niobia within Ten Minutes – Mechanochemical Reduction of Metal Oxides with Alkali Metal Hydrides

Abstract: Partially or fully reduced transition metal oxides show extraordinary electronic and catalytic properties but are usually prepared by high temperature reduction reactions. This study reports the systematic investigation of the fast mechanochemical reduction of rutile‐type TiO2 and H‐Nb2O5 to their partially reduced black counterparts applying NaH and LiH as reducing agents. Milling time and oxide to reducing agent ratio show a large influence on the final amount of reduced metal ions in the materials. For both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…The main reason for selecting NaBH 4 as the reducing agent for the true blackness of HL/BT is its reduction potential. In particular, NaBH 4 can donate highly reactive hydride ions (H + ) and create Ti 3+ defects and oxygen vacancies in the TiO 2 lattice structure . Although ascorbic acid is also a widely used reducing agent, its reduction potential is lower than that of NaBH 4 and less effective in creating defects and vacancies in the TiO 2 lattice. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for selecting NaBH 4 as the reducing agent for the true blackness of HL/BT is its reduction potential. In particular, NaBH 4 can donate highly reactive hydride ions (H + ) and create Ti 3+ defects and oxygen vacancies in the TiO 2 lattice structure . Although ascorbic acid is also a widely used reducing agent, its reduction potential is lower than that of NaBH 4 and less effective in creating defects and vacancies in the TiO 2 lattice. …”
Section: Resultsmentioning
confidence: 99%
“…In particular, NaBH 4 can donate highly reactive hydride ions (H + ) and create Ti 3+ defects and oxygen vacancies in the TiO 2 lattice structure. 34 Although ascorbic acid is also a widely used reducing agent, its reduction potential is lower than that of NaBH 4 and less effective in creating defects and vacancies in the TiO 2 lattice. 35−37 The fabrication process of plate-type HL/BT involved etching the glass template to form a hollow structure, followed by NaBH 4 reduction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The LiH molecule is also an excellent hydrogen storage material, which has important applications in the development of new energy [13][14][15]. Meanwhile, it also has been used as nuclear protection materials and reducing agents [16][17][18]. Photodissociation is the process in which a molecule absorbs photons, leading to the breaking of chemical bonds within the molecule [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The LiH molecule is also an excellent hydrogen storage material, which has important applications in the development of new energy [13–15]. Meanwhile, it also has been used as nuclear protection materials and reducing agents [16–18].…”
Section: Introductionmentioning
confidence: 99%
“…28 We have recently shown that alkali metal hydrides are readily available and powerful reducing agents for the partial reduction of rutile-type TiO 2 and monoclinic H−Nb 2 O 5 in a fast and energy efficient ball milling process. 29 Thus, the question arises whether alkali metal hydrides can also be applied as reducing agents for the mechanochemical reduction of V 2 O 5 or if a simultaneous formation of alkali metal vanadates takes place. As for the reaction of V 2 O 5 with alkali metal hydrides, no excessive studies have been reported yet.…”
Section: ■ Introductionmentioning
confidence: 99%